A nonlilear controller for ship autopilots - Tung, Le Thanh (Vietnam Journal of Mechanics, 2012)
Conventional ship autopilots are designed based on a linear ship model using pole - placement technique or linear optimal theory.  However, in operation, the ship kinematical parameters can go out the linear limits. In this paper, a nonlinear optimal control law based on aggregated variables is presented. The criterion is chosen so that the dynamic characteristics of object are included. The stability of the closed-loop  system is global according to the Lyapunov stability theory. The control law depends explicitly on ship model parameters, so that it is can be easily to tune when the parameters change.